INTERPRETATION OF THE CONFLICT BY ORDINARY CONSCIOUSNESS AND SCIENCE - Farmonova Munisakhon Valiyevna (International Journal of Innovations in Engineering Research and Technology, 2022)
This article examines interpretation of the conflict, etymology the the concept of conflict and the role of conflicts in different fields of life. Furthermore, this article reveals various types of conflicts and their main characteristics giving examples and concepts of various scientists and scholars.